Five New Species of Pezizales from Northeastern China - Zhengqing Chen; Tolgor Bau (Journal of Fungi)
Species belonging to the Pezizales are mainly saprobes in nature. They are most commonly observed in woodlands and humid environments. As a result of recent research conducted on the distribution of species in sandy areas and some National Forests Parks, five new species belonging to three genera were identified. A total of five species of disk fungi from Northeast China were identified and described based on morphological classification and molecular phylogenetics. These included Pulvinula (Pulvinula elsenensis, Pulvinula sublaeterubra), Microstoma (Microstoma jilinense, Microstoma changchunense), and Sarcoscypha (Sarcoscypha hongshiensis). Maximum likelihood and Bayesian analyses were performed using a combined nuc rDNA internal transcribed spacer region (ITS) and nuc 28S rDNA (nrLSU) dataset for the construction of phylogenetic trees. Morphological descriptions, line illustrations, and photographs of the ascocarps of these new species are provided, along with lists of the salient attributes exhibited by the species in the three genera under consideration.